2021
DOI: 10.1097/md.0000000000026466
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the emergency medical system in an area following lifting of the mandatory evacuation order after the Fukushima Daiichi Nuclear Power Plant accident

Abstract: Following the lifting of the evacuation order due to the Fukushima Daiichi Nuclear Power Plant accident, the medical demand and emergency medical system (EMS) in the area where the evacuation orders were lifted have not been well-investigated. This study aimed to evaluate the emergency transportation in such areas and compare the differences with areas that had minimal impact. Using the local EMS transport records, the characteristics of patients who were transferred by an EMS vehicle in Minamisoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…Furthermore, the evacuation order in Odaka Ward affected the Haramachi Ward in the non-evacuated areas (figure 1). Past studies have suggested that EMS response times in evacuated areas may be longer than that in non-evacuated areas after the evacuation order is lifted, [23][24][25][26] and the observed finding is not consistent with these previous studies. 26…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Furthermore, the evacuation order in Odaka Ward affected the Haramachi Ward in the non-evacuated areas (figure 1). Past studies have suggested that EMS response times in evacuated areas may be longer than that in non-evacuated areas after the evacuation order is lifted, [23][24][25][26] and the observed finding is not consistent with these previous studies. 26…”
Section: Discussioncontrasting
confidence: 57%
“…Past studies have suggested that EMS response times in evacuated areas may be longer than that in non-evacuated areas after the evacuation order is lifted, 23–26 and the observed finding is not consistent with these previous studies. 26 There are three reasons for this. First, it is possible that the outcome measure is related to total EMS time, that is, when considering T2 time alone, distance is not involved, and it depends on the ease of deciding on the receiving site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12,13] Unlike the Chernobyl accident, in the Great East Japan Earthquake (GEJE) and subsequent radiation disaster in 2011, air doses in Minamisoma were low and residents were able to return early. [14][15][16][17] Although there are some reports of emergency medical systems in evacuation areas after the disaster, [18][19][20] there are no reports of usual medical visits before and after the lifting of the evacuation order. The reopening of medical facilities is a top priority for residents when making decisions about returning to their homes.…”
Section: Introductionmentioning
confidence: 99%